Superconductivity, incoherence and Anderson localization in the crystalline organic conductor (BEDT-TTF)(3)Cl-2 center dot 2H(2)O at high pressures - Goddard, P; Tozer, S; Singleton, J; Ardavan, A; Abate, A; Kurmoo, M (2002)
The conducting properties of the pressure-induced, layered organic superconductor (BEDT-TTF)3Cl2·2H2O have been studied at 13.5 and 14.0 kbar using low temperatures, high magnetic fields and two-axis rotation. An upper critical field that is significantly larger than that expected from the Pauli paramagnetic limit is observed when the field is applied parallel to the conducting layers. The angle-dependent magnetoresistance suggests incoherent transport between the conducting layers at both pressures and the observed negative magnetoresistance at 13.5 kbar can be explained by considering Anderson localization within the layers. Further application of pressure destroys the effects of localization.